Biotopic distribution of invasive species - Dreissena polymorpha (Mollusca, Bivalvia) in lake Naroch (Belarus) in 2016-2017 - Kruk, Darya V.; Zhukava, Hanna A. (Journal of the Belarusian State University. Ecology, 2022)
The study of the population of Dreissena polymorpha (Pallas, 1771) in the Naroch Lake was carried out in 2016-2017. The distribution of the Dreissena’s population at different depths of Lake Naroch was examined at 9 transects. Dreissena was found in samples taken from 0.5 to 8 m depths and reached its maximum densities at depths of 2-6 m. As the result of the investigation, we found that the main substrate for the development of Dreissena in the lake are submerged macrophytes. The highest values of Dreissena’s abundance were observed in the samples, where Chara algae was the main substrate. This is probably due to the peculiarities of the charophyta development (incomplete dying off in winter), their morphology (strong branching of the thallus and, as a consequence, a large surface area for attaching of dreissena) and the fact that Chara algae are active carbonate precipitators (a rough surface of the thallus facilitates attachment to the plant). At the same time, the average mass of individuals of Dreissena developing on the bottom in near-shore zone was significantly greater than that of the individuals developing on macrophytes. After comparing the obtained data with the data of previous studies, it can be concluded that over the past two decades, the values of the weighted average density and biomass of Dreissena in Lake Naroch have not changed significantly.
Keywords: Dreissena polymorpha; biotopic distribution; population density; Naroch Lake; submerged macrophytes